Comparison of enzymatic and precipitation treatments for gluten-free craft beers production. (October 2018) - Fanari, Mauro; Forteschi, Mauro; Sanna, Manuela; Zinellu, Manuel; Porcu, Maria Cristina; Pretti, Luca
Abstract: Celiac disease and non-celiac gluten sensitivity are both related to gluten consumption. In sensitive subjects, gluten triggers an immune-mediated enteropathy for which no therapy is yet available. Beer must be avoided by gluten sensitive subjects, since it is generally made from gluten containing grains such as barley and wheat. In this study we compared two different deglutinization treatments on an American India Pale Ale, brewed on a craft beer pilot plant: an enzymatic process based on Aspergillus niger prolyl endopeptidase and a precipitation process by silica gel. The gluten amount in all stages of brewing, and the effects of treatments on standard quality attributes, chemical composition and sensory profile were evaluated. Both treatments were able to reduce gluten level below 20 ppm, showing a different behavior. Only slight differences were observed in the chemico-physical characteristics of treated and untreated beers, whereas sensory analysis did not highlight any change. Industrial relevance: Considering the massive increase of microbreweries and the grown of gluten-free products market, two different deglutinization treatment were compared in pilot plant production of craft beer. Results show how it is possible to produce a gluten-free beer from traditional ingredients. The slight differences observed between treatments had no impact on the sensory profile, allowing to brew high quality gluten-free beers. Highlights: Gluten-free craft beer can be produced from traditional ingredients. Gluten content decreases in brewing stages. Beer deglutinization treatments let unaltered the sensory profile of the original recipe.